Perspektif Etika Bisnis Islam Terhadap Pengelolaan Peternakan Ayam Di Desa Pinggir Air - Angriani, Weny (ISTIKHLAF: Jurnal Ekonomi, Perbankan dan Manajemen Syariah, 2024)
Considering that the egg products of purebred chickens of farmers in waterfront villages have not been able to meet the standard needs of around 20% of the local market needs, so that purebred chicken eggs are imported from outside the region to meet egg needs. The lack of supply from within this area is not able to meet local needs, making the opportunities for the waterfront village community to develop laying hen farm management very wide open. This research is to find out the Perspective of Islamic Business Ethics on the implementation of Chicken Farm Management. The research method used is qualitative research with sample determination. The key informant in this study is a chicken farmer in Pinggir Air. Non-key informants are people who are considered to know the problem being researched. The result of this study is an indicator of the management of chicken farms in Pinggir Air Village, this chicken farming business uses land and personal capital partly from loans from conventional banks. This chicken farming marketing system uses a direct marketing system. The perspective of Islamic business ethics on the implementation of chicken farm management in Pinggir Air Village has fully applied the principles of Islamic business ethics based on unity (monotheism or unity) by not leaving the essence of worship to God, as well as establishing a balance in determining fair egg prices for all consumers and being responsible and honest in determining and maintaining egg quality.